2020
DOI: 10.1108/mrjiam-06-2020-1046
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on exploring the critical success factors for developing COVID-19 preventive strategy with an economy centric approach

Abstract: Purpose In the wake of COVID-19, most of the countries at present, are in a dilemma whether to extend lockdown at the cost of economy or to improve the hard-hit economy by lifting the lockdown. It is indicated by the reputed organizations and medical fraternity that corona will stay here for a longer period contrary to the earlier assumptions. Hence the purpose of this study is to suggest a strategy which balances both preventive measures and economic losses to control the pandemic. Design/methodology/approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 50 publications
2
37
0
2
Order By: Relevance
“… Maqbool and Khan (2020) ’ study concluded that lack of resources for implementing public health and social measures is the most influential barrier. In another study, Kashyap and Raghuvanshi (2020) identified the critical success factors for developing COVID-19 preventive strategies to control the pandemic using the fuzzy logic based DEMATEL method.…”
Section: Literature Revie Wmentioning
confidence: 99%
“… Maqbool and Khan (2020) ’ study concluded that lack of resources for implementing public health and social measures is the most influential barrier. In another study, Kashyap and Raghuvanshi (2020) identified the critical success factors for developing COVID-19 preventive strategies to control the pandemic using the fuzzy logic based DEMATEL method.…”
Section: Literature Revie Wmentioning
confidence: 99%
“…Regarding the mix between personal and professional life in particular, Ratten (2020a) and Sheth (2020) believe that the "work from home modality" will be a new trend, and many services will be developed to consider this new reality. Changes in people's behaviour are involved in this work modality and need to be debated, as argued by Kashyap and Raghuvanshi (2020) and Madero G omez et al (2020). Another interesting study about consumer behaviour changes during the social distancing caused by COVID-19 pandemic is presented by Kirk and Rifkin (2020).…”
Section: Reflections and Guideline Proposalsmentioning
confidence: 99%
“…According to Kashyap and Raghuvanshi (2020), among them, government grants as a prevention strategy would help restructure the business related to European start-ups as stated below.…”
Section: The Mitigation Measures Taken By the Government To Revitalise The Economiesmentioning
confidence: 99%
“…France has even put together a fund of 4 billion euro to support their start-ups. Start-up companies have always taken more risk than other companies as mentioned by Kashyap and Raghuvanshi (2020). They capitalise on innovation and brilliance.…”
Section: Innovative Ideas To Help the European Industry Recover Fastermentioning
confidence: 99%